Protocol for a randomized clinical trial: telephone-based psychoeducation and support for female informal caregivers of patients with dementia - Andressa Hermes-Pereira; Patrícia Ferreira; Matheus Canellas Fonseca Barbosa dos Santos; Pedro Alves Fagundes; Ana Paula Bresolin Gonçalves; Dimitris Varvaki Rados; Raphael Machado Castilhos; Lucas Porcello Schilling; Márcia Lorena Fagundes Chaves; Roberto Umpierre; Renata Kochhann; Artur Francisco Schumacher-Schuh (Brazilian Society of Geriatrics and Gerontology, 2022)
OBJECTIVE: The burden felt by informal caregivers of patients with dementia is a source of physical, emotional, and financial problems. Face-to-face interventions for caregivers have accessibility limitations that may prevent them from receiving adequate care. Telehealth tools can be a solution to this problem. We will compare a telephone psychoeducational and support intervention protocol to usual care for informal female caregivers of patients with dementia treated at Brazilian specialized outpatient clinics. METHODS: In this single-blind randomized clinical trial, the intervention group will receive one weekly call for 8 weeks that addresses issues such as disease education, communication with the patient, and problematic behaviors. The control group will receive printed material on problematic behaviors in dementia. The primary outcome will be the difference in caregiver burden between baseline and 8 weeks, which will be assessed by blinded investigators through the Zarit Burden Interview scale. Caregiver burden at 16 weeks after baseline, depression, anxiety, and quality of life at 8 and 16 weeks are secondary outcomes. CONCLUSIONS: We expect the intervention to reduce caregiver burden. These results could lead to public health programs for improving dementia care in lower-middle-income countries. Ethics and dissemination: This trial was approved by an independent ethics committee. The results will be published in an international peer-reviewed medical journal. Trial registration number: NCT03260608.